Art Therapy Education Teaching, Training, and Research - Aylat Yaguri, Tamar; Merari, Dalia (Cambridge Scholars Publishing, 2021)
Art and artmaking are at the basis of art therapy as a healing practice. Teachers of art therapy emphasize the role of the creative process and the symbolic use of materials in the training of art therapy students. This volume suggests an innovative research approach that examines different art therapy teaching and training practices, and studies them as parts of one picture.